Burgers and their Settlements in Ambon City Historical Study of Colonial Cities to Music Cities - Pusparani, Rina; Kempa, Titin (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
The problems that will be studied in this research are as follows: (1) What was life like for burgers and their settlements in Ambon City during the colonial period? (2) What was the condition of the people and settlements in the city of Ambon during the post-independence government period until now? To get answers to these problems, the research method used is the historical method which consists of four stages, namely heuristics, criticism, interpretation and historiography. The purpose of this research is to apply urban historical studies using historical research methods. Practically, this research will be useful, especially for government practitioners and policy makers, especially in the Ambon City Government, namely related agencies, as well as for state governments in particular and in the Ambon Island and Lease Island Regions. The result of this research is that burgers are city residents. Those who live in the city of Ambon are both Dutch and European, Chinese, Arabs and Natives. They are classified into three types of burgers, namely Europeesche Burgers, Inlandsche Burgers and Moorsche Burgers. Due to their increasing number, the resident government arranged settlements, namely special settlements for burgers, including Kampung Mardika, Urimessing, Galala, Hunut, Lata, Lateri, Halong, Negeri Lama, Nania, Rumah Tiga (Nipah), Poka, and Waiheru.